Economics and environmental change the challenges we face - Tisdell, Clement A. (Cheltenham, UK ; Northampton, MA : Edward Elgar Pub., 2017)
In this innovative book, Clement Tisdell adopts a holistic approach, combining economic, social, biophysical and historical considerations to analyse the economic origins of major contemporary environmental problems, especially those associated with climate change. The ability of humankind to respond effectively to these problems is assessed in a unique and lucid fashion. The depth and nature of social embedding is identified as the major (but not the only) barrier to dealing with human-induced environmental change. In a thought-provoking manner, the book provides discussions of: the relationships between the nature of economic development, social and environmental change; the limited policy guidance provided by debates about the desirability of sustainable development; the shortcomings of economic criteria for valuing environmental and social change; and social embedding as the prime impediment to humanity responding adequately to many of its current environmental problems. Given its interdisciplinary nature, this book will appeal to economists, sociologists, geographers, social historians and political scientists alike. Natural scientists who are interested in socio-economic aspects of environmental change will also find this a captivating read.
Contents: Preface -- 1. Cconomics and environmental change : an overview -- 2. Growing economic activity and environmental change : historical and general perspectives. -- 3. Sustainable (economic) development. what is it? is it desirable? can it be achieved and if so, how? -- 4. Values, economic valuation, and the assessment of environmental and economic change. -- 5. Social embedding : its nature and role in determining our economic and environmental future. -- 6. Consumers' sovereignty : significant failures : why consumers' demands for environmental, human and animal protection are often unmet. -- 7. Biological conservation and human-induced environmental change : contemporary socio-economic challenges -- 8. Climate change : general aspects, and alterations in energy sources and use as responses -- 9. Agriculture and environmental change, especially climate change : economic challenges. -- 10. Marine ecosystems and global climate change : economic consequences, resilience and adjustment.
Description based on print record.
Keywords: Global environmental change -- Economic aspects; Electronic books